Effects of a 12-week whole-grain or refined wheat intervention on plasma acylcarnitines, bile acids and signaling lipids, and association with liver fat: A post-hoc metabolomics study of a randomized controlled trial - Gijbels, Anouk; Schutte, Sophie; Esser, Diederik; Wopereis, Suzan; Gonzales, Gerard Bryan; Afman, Lydia A. (Frontiers in Nutrition, 2022)
Background: We previously showed that whole-grain wheat (WGW) consumption had beneficial effects on liver fat accumulation, as compared to refined wheat (RW). The mechanisms underlying these effects remain unclear. Objective: In this study, we investigated the effects of WGW vs. RW consumption on plasma metabolite levels to explore potential underlying mechanisms of the preventive effect of WGW consumption on liver fat accumulation. Methods: Targeted metabolomics of plasma obtained from a concluded 12-week double-blind, randomized controlled trial was performed. Fifty overweight or obese men and women aged 45-70 years with mildly elevated levels of plasma cholesterol were randomized to either 98g/d of WGW or RW products. Before and after the intervention, a total of 89 fasting plasma metabolite concentrations including acylcarnitines, bile acids, and signaling lipids were quantified by UPLC-MS/MS. Intrahepatic triglycerides (IHTG) were quantified by 1H-MRS, and multiple liver markers were assessed, including circulating levels of β-hydroxybutyrate, alanine transaminase, aspartate transaminase, γ-glutamyltransferase, serum amyloid A, and C-reactive protein. Results: The WGW intervention increased plasma concentrations of four out of 52 signaling lipids - lysophosphatidic acid C18:2, lysophosphatidylethanolamine C18:1 and C18:2, and platelet-activating factor C18:2 - and decreased concentrations of the signaling lipid lysophosphatidylglycerol C20:3 as compared to RW intervention, although these results were no longer statistically significant after FDR correction. Plasma concentrations of the eight bile acids and 29 acylcarnitines that we quantified were not affected by WGW or RW intervention. Changes in the above-mentioned metabolites were not correlated to change in IHTG upon the intervention. Conclusions: The plasma acylcarnitines, bile acids, and signaling lipids were not robustly affected by the WGW or RW interventions, which makes them less likely candidates to be directly involved in the mechanisms that underlie the protective effect of WGW consumption or detrimental effect of RW consumption on liver fat accumulation. This trial was registered at ClinicalTrials.gov as NCT02385149.